2019
DOI: 10.4103/ua.ua_117_18
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fluid absorption following percutaneous nephrolithotomy: Changes in blood cell indices and electrolytes

Abstract: Background and Aims: Effects of fluid absorption on hematological profile in the immediate postoperative period in patients undergoing percutaneous nephrolithotomy (PCNL) have not been given due importance. Considering the limited number of studies available, we conducted this study to evaluate the changes in hemodynamics, complete blood count (CBC), and electrolytes in patients undergoing PCNL using normal saline for irrigation in the prone position. Furthermore, we evaluated the common factors k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 13 publications
(22 reference statements)
0
5
0
2
Order By: Relevance
“…Meanwhile, when the operation time is prolonged, the amount of perfusate used can accordingly increase, which will lead to the absorption of a large amount of perfusate (36). Several previous studies (34,(37)(38)(39) have also found that the amount of fluid absorption in PCNL is positively correlated with the perfusion time. With the damage of the renal pelvis mucosa caused by the crushing process, the perfusate easily flows into the blood through the renal sputum, and bacteria or toxins can enter the blood by this pathway easily.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, when the operation time is prolonged, the amount of perfusate used can accordingly increase, which will lead to the absorption of a large amount of perfusate (36). Several previous studies (34,(37)(38)(39) have also found that the amount of fluid absorption in PCNL is positively correlated with the perfusion time. With the damage of the renal pelvis mucosa caused by the crushing process, the perfusate easily flows into the blood through the renal sputum, and bacteria or toxins can enter the blood by this pathway easily.…”
Section: Discussionmentioning
confidence: 99%
“…And the longer the operation, the more serious the situation (32,33). Under the condition of hypothermia, the patient's cardiovascular function changes, coagulation function disorder, which can increase intraoperative blood loss and tissue damage (34,35). Meanwhile, when the operation time is prolonged, the amount of perfusate used can accordingly increase, which will lead to the absorption of a large amount of perfusate (36).…”
Section: Discussionmentioning
confidence: 99%
“…Irrigating fluid absorption, bleeding and haemodynamic abnormalities are common. PNL-related complications are common, and patient recovery from anaesthesia is challenging, especially in high-risk groups ( 19 , 20 ). There are few studies on PNL-related blood loss, haemodynamic changes and electrolyte levels.…”
Section: Discussionmentioning
confidence: 99%
“…1 Kĩ thuật bơm rửa nước đồng thì trong quá trình tán sỏi thận nhằm tạo điều kiện thuận lợi cho quá trình can thiệp nhưng lại làm tăng nguy cơ hấp thu dịch rửa vào cơ thể, dẫn đến quá tải dịch, rối loạn điện giải, toan kiềm. 2,3 Mặc dù, một số tác giả nhấn mạnh tầm quan trọng của việc theo dõi khối lượng nước rửa hấp thụ, thời gian và tốc độ chảy của dịch rửa trong tán sỏi qua da nhưng vẫn chưa tìm thấy có mối liên quan nào cụ thể nào với nồng độ Natri, Kali, pH và BE trong máu sau phẫu thuật. 4,5 Ở Việt Nam, trong những năm gần đây phương pháp tán sỏi thận qua da đang ngày càng phổ biến và vẫn chưa có các nghiên cứu tìm hiểu các yếu tố liên quan đến sự thay đổi về khí máu, nước điện giải và thăng bằng kiềm toan trên những bệnh nhân tán sỏi qua da.…”
Section: đặT Vấn đềunclassified
“…Kết quả này của chúng tôi cũng tương tự với các nghiên cứu của các tác giả trên thế giới như Mohta, 5 Atici,6 Teckul, Tác giả Mohta và cộng sự (2008) cho thấy không có mối liên quan nào giữa thời gian tán sỏi, thể tích dịch rửa và thể tích dịch rửa hấp thu với nồng độ Natri, Kali, pH và BE trong máu sau phẫu thuật 5. Tác giả Saxena (2019) nghiên cứu trên 40 bệnh nhân tán sỏi qua da cũng không tìm thấy mối tương quan giữa lượng dịch tưới rửa, thời gian tán sỏi với nồng độ Na máu (r = -0,09 ; p > 0,05) 3. Điều này cũng gần tương tự kết quả nghiên cứu của chúng tôi cho thấy không có sự tương quan giữa nồng độ Na, Kali với các yếu tố trên (p > 0,05).…”
unclassified